2006
DOI: 10.1097/01.aids.0000247580.16073.1b
|View full text |Cite
|
Sign up to set email alerts
|

Access to adequate nutrition is a major potential obstacle to antiretroviral adherence among HIV-infected individuals in Rwanda

Abstract: Despite the massive expansion of antiretroviral drugs in Africa, little is known about the resulting changes in sexual behavior or obstacles to antiretroviral therapy (ART) adherence. Our evaluation of Rwandan adults on ART found no increase in risky sexual behaviors, but an obstacle to ART initiation and adherence for 76% of patients was a fear of developing too much appetite without enough to eat. Access to adequate nutrition may be a major determinant for long-term adherence to ART.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
95
1
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(103 citation statements)
references
References 15 publications
6
95
1
1
Order By: Relevance
“…This association has fostered a great deal of interest because of the links between poor adherence and HIV suppression, immunological decline and the progression of HIV to AIDS . A growing number of studies have demonstrated or at least called attention to the important links between food insecurity and ART initiation, adherence, and consistency of ARV consumption (see, e.g., Au et al, 2006;Nachega et al, 2006;Hardon et al, 2007;Olupot-Olupot et al, 2008;Sanjobo et al, 2008;Kalofonos, 2010). In each of these studies, food concerns took on different dimensions.…”
Section: Food Insecurity and Hiv/aidsmentioning
confidence: 99%
“…This association has fostered a great deal of interest because of the links between poor adherence and HIV suppression, immunological decline and the progression of HIV to AIDS . A growing number of studies have demonstrated or at least called attention to the important links between food insecurity and ART initiation, adherence, and consistency of ARV consumption (see, e.g., Au et al, 2006;Nachega et al, 2006;Hardon et al, 2007;Olupot-Olupot et al, 2008;Sanjobo et al, 2008;Kalofonos, 2010). In each of these studies, food concerns took on different dimensions.…”
Section: Food Insecurity and Hiv/aidsmentioning
confidence: 99%
“…The following set of twelve food groups was used to calculate the IDDS: (i) cereals; (ii) roots and tubers; (iii) pulses and legumes/nuts; (iv) vegetables; (v) fruits; (vi) meat and poultry; (vii) eggs; (viii) fish and seafood; (ix) milk and milk products; (x) oils and fats; (xi) sugar and sweets; and (xii) condiments and miscellaneous. Three categories of dietary diversity were created, based on IDDS: (i) low (0-4), (ii) medium (5-8) and (iii) high (9)(10)(11)(12).…”
Section: Individual Diet Qualitymentioning
confidence: 99%
“…Food insecurity is one of the multiple barriers that individuals face in initiating and adhering to long-term medical therapies such as ART and DOTS, especially in resourcelimited settings [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]. Other patient-related barriers include the complexity of the medication regimen [18], emotional distress [7], illness costs to households [19], stigma [20], health beliefs and poverty [4], limited knowledge of the disease [21], difficulty remembering [22], intentional non-adherence due to adverse drug reactions [23] and harmful use of alcohol [24].…”
Section: Introductionmentioning
confidence: 99%
“…Adherence support strategies may include directly observed treatment, education and counseling, patient reminder and late patient tracer systems, and incentive or enabler 1 systems, including food assistance. It is important to note that food assistance often has a dual role.…”
Section: Introductionmentioning
confidence: 99%